Wherever I go - Copp, Mary Wagley (Atheneum Books for Young Readers, 2019)
"A hopeful and timely picture book about a spirited little girl living in a refugee camp. Of all her friends, Abia has been at the Shimelba Refugee Camp the longest--seven years, four months, and sixteen days. Papa says that's too long and they need a forever home. Until then, though, Abia has something important to do. Be a queen. Sometimes she's a noisy queen, banging on her drum as she and Mama wait in the long line for rice to cook for dinner. Sometimes she's a quiet queen, cuddling her baby cousin to sleep while Auntie is away collecting firewood. And sometimes, when Papa talks hopefully of their future, forever home, Abia is a little nervous. Forever homes are in strange and faraway places--will she still be a queen? Filled with hope, love, and respect, Wherever I Go is a timely tribute to the strength and courage of refugees around the world."--Provided by publisher.